CCR5 expression, haplotype and immune activation in protection from infection in HIV‐exposed uninfected individuals in HIV‐serodiscordant relationships. Issue 4 (24th May 2017) - Jaumdally, Shameem Z.; Picton, Anabela; Tiemessen, Caroline T.; Paximadis, Maria; Jaspan, Heather B.; Gamieldien, Hoyam; Masson, Lindi; Coetzee, David; Williamson, Anna‐Lise; Little, Francesca; Gumbi, Pamela P.; Passmore, Jo‐Ann S.
Abstract : Interactions between systemic inflammation and T‐cell activation in resistance to HIV infection were studied. HIV‐negative exposed individuals had significantly lower frequencies of CCR5 + CD4 + and CD8 + T cells than unexposed individuals, and plasma concentrations of interleukin‐2, interferon‐ γ and granulocyte–macrophage colony‐stimulating factor were lower in exposed compared with unexposed individuals. This study identified lower T‐cell CCR5 expression and plasma cytokine concentrations as the dominant signature of resistance to HIV infection in this cohort of exposed but uninfected individuals. Summary: Several host factors have been implicated in resistance to HIV infection in individuals who remain HIV‐seronegative despite exposure. In a cohort of HIV‐serodiscordant heterosexual couples, we investigated interactions between systemic inflammation and T‐cell activation in resistance to HIV infection. Males and females in stable long‐term relationships with either HIV‐infected or uninfected partners were recruited, blood T‐cell activation (CD38, HLA‐DR, CCR5 and Ki67) and plasma cytokine concentrations were evaluated. The HIV‐negative exposed individuals had significantly lower frequencies of CCR5 + CD4 + and CD8 + T cells than unexposed individuals. Mean fluorescence intensity of CCR5 expression on CD4 + T cells was significantly lower in HIV‐negative exposed than unexposed individuals. Protective CCR5 haplotypes (HHA/HHF*2, HHF*2/HHF*2, HHC/HHF*2, HHA/HHA, HHA/HHC and HHA/HHD) tended to be over‐represented in exposed compared with unexposed individuals (38% versus 28%, P = 0·58) whereas deleterious genotypes (HHC/HHD, HHC/HHE, HHD/HHE, HHD/HHD and HHE/HHE) were under‐represented (26% versus 44%; P = 0·16). Plasma concentrations of interleukin‐2 ( P = 0·02), interferon‐ γ ( P = 0·05) and granulocyte–macrophage colony‐stimulating factor ( P = 0·006) were lower in exposed compared with unexposed individuals. Activation marker expression and systemic cytokine concentrations were not influenced by gender. We conclude that the dominant signature of resistance to HIV infection in this cohort of exposed but uninfected individuals was lower T‐cell CCR5 expression and plasma cytokine concentrations.